PELATIHAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN KANCING GEMERINCING - Tetty Natalia Sipayung (Bajang Institute, 2021)
Teachers as educators are expected to help students improve their knowledge. Therefore, it is necessary for teachers to know the application of learning models, especially in mathematics, which is one of the important subjects in the field of education. Many teachers use conventional learning models. It is less effective and boring for students. One of the learning models that are considered very good to be applied is the cooperative learning model assisted by jingling buttons. Through community service activities in class VII SMP HKBP Lubuk Pakam, the learning model was applied. The form of activity is carried out with lectures and practice. The result is that teachers and students understand the application of the jingling button-based learning model and the students are also seen to be active and enthusiastic in learning, even trying hard to answer the math problems given correctly and quickly until the buttons obtained by the group run out.